2019
DOI: 10.1158/1055-9965.epi-18-0811
|View full text |Cite
|
Sign up to set email alerts
|

Population Health Assessment in NCI-Designated Cancer Center Catchment Areas

Abstract: In May 2016, the NCI announced supplemental funding for NCI-Designated Cancer Centers to conduct research to better characterize populations within cancer center catchment areas. The initiative was intended to support primary data collection efforts to better define and describe cancer center catchment areas using a multilevel population health framework. The long-term goal was to facilitate collaborations in which researchers, providers, public health practitioners, and nonprofit organizations could utilize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…This study sample was identified from the 1000 participants in the Population Health Assessment in Cancer Center Catchment Areas (PHA) study (IRB#17-8005) [ 29 ], a National Cancer Institute effort to support survey development using nationally validated instruments [ 30 ], data collection, and data linkage efforts that could help define and describe underserved cancer center populations across the US [ 29 ]. For this effort, a variety of sampling approaches were supported to capture often-understudied populations [ 29 ]. At the center of the Fox Chase Cancer Center (FCCC) catchment area of southeastern Pennsylvania and southern New Jersey is Philadelphia.…”
Section: Methodsmentioning
confidence: 99%
“…This study sample was identified from the 1000 participants in the Population Health Assessment in Cancer Center Catchment Areas (PHA) study (IRB#17-8005) [ 29 ], a National Cancer Institute effort to support survey development using nationally validated instruments [ 30 ], data collection, and data linkage efforts that could help define and describe underserved cancer center populations across the US [ 29 ]. For this effort, a variety of sampling approaches were supported to capture often-understudied populations [ 29 ]. At the center of the Fox Chase Cancer Center (FCCC) catchment area of southeastern Pennsylvania and southern New Jersey is Philadelphia.…”
Section: Methodsmentioning
confidence: 99%
“…Data-driven solutions are part of the future of healthcare operations and can be part of the solution to inform outreach and research priorities ( 16 ). The KU Cancer Center’s goal is to use data available in OPTIK to summarize the trends and metrics of its bi-state catchment population without having to rely on national trends to influence policy decisions ( 17 , 18 ). This paper outlines the need for and the process of data consolidation and visualization building at the core of OPTIK’s key functions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, current recommendations for liver cancer prevention focus on targeting high risk, minority populations including: Hispanics, Blacks, and those born between 1950 and 1959 who are at risk for HCV infection ( Petrick, Kelly, Altekruse, McGlynn, & Rosenberg, 2016 ). As a result, U.S. cancer centers, who are often tasked with implementing cost-effective educational and behavioral interventions for liver cancer prevention, commonly utilize publically-available neighborhood demographic data from the U.S. Census to identify these vulnerable communities in their catchment—defined as the neighborhoods where their patients reside ( Blake, Ciolino, & Croyle, 2019 ). Neighborhood data is used because studies suggest an individual’s demographics are similar to the neighborhood in which they live, particularly at smaller geographic areas ( Tunstall, 2005 ).…”
Section: Introductionmentioning
confidence: 99%